Granulomatosis with Polyangiitis Misdiagnosed as IgA Vasculitis in a Child - Sheida Amini; Mohsen Jari (Case Reports in Pediatrics)
Background. Granulomatosis with polyangiitis (GPA) with early manifestations simulating IgA vasculitis is a very rare childhood systemic disease. Case Presentation. A 10-year-old boy presented initially with cutaneous, skeletal, and abdominal signs suggestive of IgA vasculitis. Over time, the worsening of skin ulcers, orchitis, and renal involvement led to the diagnosis of GPA according to cytoplasmic positive antineutrophil cytoplasmic antibodies and renal biopsy. Conclusion. Clinicians should be awared of the diagnostic pitfalls when making a clinical diagnosis of IgA vasculitis in children older than 7 years.